THE EFFECTIVENESS OF GOOGLE CLASSROOM AS LEARNING MEDIA IN TEACHING DESCRIPTIVE TEXT - Tendean, Junior F.; Liando, Nihta V. F.; Olii, Sanerita T. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
Google Classroom is a costless platform that facilitates cooperation between educators and learners. Teachers have the ability to establish a virtual learning environment, extend invitations to students to join the class, and thereafter generate and disseminate assignments. Google Classroom facilitates communication between students and teachers, allowing them to engage in discussions over assignments, while also enabling teachers to monitor students’ academic advancement. This study employs a quantitative research approach, utilizing a test instrument and following a pre-experimental design with a single group undergoing both pre-test and post-test assessments. A pre-test was administered prior to the treatment, while a post-test was given after the treatment. The pre-test and post-test were utilized to assess the students’ proficiency in comprehending descriptive text through the usage of Google Classroom as a learning medium. The research revealed that a total of twenty students took part in the test. During the pre-test, a single student achieved the maximum score of 65, while two students obtained the lowest score of 30. One student achieved a perfect score of 100 on the post-test, while another student scored 75 or higher. The average pre-test (T1) score was 44, whereas the average post-test (T2) score was 87. The results of the pre-test indicate that the students’ knowledge is still somewhat deficient. Subsequently, the post-test results indicated a noticeable improvement in the pupils’ performance following the implementation of the researcher’s remedy. Ultimately, The findings of this study indicate that Google Classroom is highly efficacious in facilitating the instructional process for students